The Austrian ECOLOG Schools Network - Franz Rauch; Mira Dulle (Universidade de Lisboa, 2023)
This paper describes networking for education for sustainable development within the Austrian ECOLOG-schools network. It discusses theoretical concepts of Education for Sustainable Development and school development from an Austrian perspective, as well as networks in education in general and the organisation of the ECOLOG-network in particular. ECOLOG is a programme and network for the greening of schools and education for sustainability in Austria. For 25 years, over 700 ECOLOG schools and 13 colleges of teacher education have been integrating an ecological approach into their everyday school life and school development. Throughout the ECOLOG-schools network's existence, a series of evaluations, inquiries, and studies have been produced (Rauch & Pfaffenwimmer, 2020). Based on these evaluations and to obtain current quantitative data on the implementation of ECOLOG at the participating schools, a questionnaire survey was sent to all ECOLOG school coordinators with 154 respondents (25% response rate) in the school year 2018/19, with the aim of deriving relevant measures to support ECOLOG schools. The results show that the coordinators implemented the ECOLOG principles in their everyday school life through environmentally conscious actions, while pupils learned how to deal with limited resources and were exposed to new ways of thinking and working. However, there is still room for improvement, for instance in shaping cooperation with out-of-school partners.